Loneliness and maternal burden of care in times of COVID-19 pandemic in the light of psychoanalytic listening to bonds - Emidio, Thassia Souza [UNESP]; Okamoto, Mary Yoko [UNESP]; dos Santos, Manoel Antônio (FapUNIFESP (SciELO), 2023)
This study aimed to analyze how domestic confinement resulting from the COVID-19 pandemic impacted motherhood among working women in a home office situation. This was an exploratory study, employing a longitudinal design and the theoretical framework of the psychoanalysis of bonds. Between April and July 2020, online interviews were conducted with 20 mothers from middle social strata, aged 29 to 45. One year later, new interviews were conducted with 10 participants, all transcribed and subjected to thematic analysis. The results showed that, compared to the initial period of the pandemic, mothers were close to physical and psychological exhaustion due to continuous overwork and lack of social and family support. These factors had deleterious impacts on the participants’ mental health, leading to reports of suffering and psychological helplessness. The search for medicalization reveals an individualized perception of the problem and an attempt to demonstrate stoicism to mitigate the suffering resulting from this experience.
Soledad y sobrecarga materna en tiempos de pandemia COVID-19 a la luz de la escucha psicoanalítica de los vínculos
Solidão e Sobrecarga Materna em Tempos de Pandemia de COVID-19 à Luz da Escuta Psicanalítica dos Vínculos
Keywords: COVID-19; maternity; mental health; pandemic; psychoanalysis of bonds